Implementing Precaution in Benefit-Cost Analysis : The Case of Deep Seabed Mining - Krutilla, Kerry (World Bank, Washington, DC, 2020)
The authors wish to thank the World Bank for financial support and accesses to information sources. For many helpful comments and suggestions, the authors are also grateful to Nicholas Treich and other conferees at the European Society for Benefit-Cost Analysis first annual meeting at the Toulouse School of Economics, November 2019; Bryan Land and other participants at a World Bank stakeholder meeting in Sydney Australia, November 2018; Jonathan Wiener, of Duke University; Steve Grimsley, a Senior Geophysical Advisor, previously of Hess Corporation; and Chris Colton, founder of Hexis Energy Trading, LLC. Carl Brown-Grimm and Shu-Chuan Chiu provided essential research assistance. Notwithstanding this excellent input, the authors bear exclusive responsibility for the findings, judgements, and conclusions in this article.